2007
DOI: 10.1038/sj.gene.6364395
|View full text |Cite
|
Sign up to set email alerts
|

Heritability of serum hs-CRP concentration and 5-year changes in the Stanislas family study: association with apolipoprotein E alleles

Abstract: We aimed at estimating additive genetic heritability, household component effect and the influence of common alleles of the apolipoprotein E gene (APOE) on serum high-sensitivity C-reactive protein (hs-CRP) concentrations and the subsequent changes over 5 years. A sub-sample of 320 nuclear families was randomly selected from the Stanislas Family Study. Serum hs-CRP concentration was measured by immunonephelometry at entrance and after 5 years. APOE alleles were determined by restriction fragment length polymor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
5
0

Year Published

2009
2009
2015
2015

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 39 publications
2
5
0
Order By: Relevance
“…In agreement with other studies we found that serum CRP was lower in subjects with ε4 haplotypes [25,28,29,30]. This association was present after adjusting for other risk factors, such as age, diabetes, CHD and hypertension.…”
Section: Discussionsupporting
confidence: 93%
“…In agreement with other studies we found that serum CRP was lower in subjects with ε4 haplotypes [25,28,29,30]. This association was present after adjusting for other risk factors, such as age, diabetes, CHD and hypertension.…”
Section: Discussionsupporting
confidence: 93%
“…7,25,37 In the Stanislas Family Study of 320 nuclear families, variance component analysis did not reveal the presence of a significant genetic effect to variation in hs-CRP. 8 In the Jackson Heart Study, the heritability of hs-CRP in blacks reached 45% after adjustment for age, sex, and BMI. 9 Comparable heritability levels have been reported in Japanese Americans (30%), twins many of which with hypertension (56%) and siblings from the Diabetes Heart Study (37% after adjustment for age, sex, ethnicity, and BMI).…”
Section: Evidence For Genetic Covariation Among Cvd Risk Factorsmentioning
confidence: 99%
“…3D). In this instance, a false-negative association may be due to failure to account for a second gene that modifies the levels of the biomarker of interest, e.g., a SNP in the promoter of the IL-6 gene that associates with serum IL-6 levels [31] has been shown to correlate more strongly with CRP than IL-6 levels [32], and ApoE alleles can also influence CRP concentrations [33,34]. Illustrating gene-environmental interactions, a recent study showed that environmental factors modify the effects of the functional IL-6 promoter SNP [35].…”
Section: Considerations For Mendelian Randomizationmentioning
confidence: 99%